2014
DOI: 10.1515/corrrev-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Microbially influenced corrosion of steels by Pseudomonas aeruginosa

Abstract: Microbially influenced corrosion (MIC) is a destructive type of corrosion that is initiated, facilitated, or accelerated by the presence and metabolic activity of bacteria. MIC of steels is a great issue in many industries such as marine, freshwater systems, and gas/oil pipelines. Pseudomonas aeruginosa is one of the aerobic slime-forming bacteria that are ubiquitous in marine environment that corrode steel structures. This article aims to provide a review on MIC of steels caused by bacteria, mostly in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…P. aeruginosa is said to be the pioneer colonizer in the process of biofilm formation in the aquatic environment (San et al 2014) and it has been confirmed that it is an important corrosive bacterium in the marine environment, resulting in economic and environmental damage . Researchers have investigated the MIC of some carbon steels and SSs and found these materials were severely corroded by P. aeruginosa (Yuan & Pehkonen 2007;Abdolahi et al 2014;Hamzah et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa is said to be the pioneer colonizer in the process of biofilm formation in the aquatic environment (San et al 2014) and it has been confirmed that it is an important corrosive bacterium in the marine environment, resulting in economic and environmental damage . Researchers have investigated the MIC of some carbon steels and SSs and found these materials were severely corroded by P. aeruginosa (Yuan & Pehkonen 2007;Abdolahi et al 2014;Hamzah et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some species are known to be MIC-related bacteria. For example, Pseudomonas aeruginosa can induce MIC on steel and stainless steel under aerobic conditions [10,38,39]; sulfate-reducing bacteria (SRB) such as Desulphovibrio vulgarius produce H 2 S, which triggers iron ionization under anaerobic conditions [40,41]; sulfur-oxidizing bacteria such as Acidithiobacillus thiooxidans (old name: Thiobacillus thiooxidans) produce sulfuric acid which increases acidity and induces iron oxidization [6,42,43]; and iron-oxidizing bacteria such as Callionella and Leptothrix oxidize iron [6,44]. Desulphovibrio, Acidithiobacillus, Pseudomonas, Callionella, and Leptothrix belong to the orders Desulfovibrionales, Acidithiobacillales, Pseudomonadales, Nitrosomonadales, and Burkholderiales, respectively.…”
Section: Cu-coatedmentioning
confidence: 99%
“…The rate of penetration depends on the barrier quality of the coating, but for most organic coating, the result of coating being completely detached is usually inevitable. In this research, two microbiologically influenced corrosion (MIC) bacteria were selected from the both Gram-positive and Gram-negative class, which were Staphylococcus aureus (+) and Pseudomonas aeruginosa (−), respectively [8][9][10]. This study aimed to develop a highly efficient organic coating using the plant extract of Leucaena leucocephala or river tamarind as the additive.…”
Section: Introductionmentioning
confidence: 99%